Desenvolvimento de sistemas de pastas leves para aplicação em cimentação de poços petrolíferos com baixo gradiente de fratura - Araujo Filho, Romero Gomes da Silva (2012)
All around the world, naturally occurring hydrocarbon deposits, consisting of oil and gas contained within rocks called reservoir rocks , generally sandstone or carbonate exists. These deposits are in varying conditions of pressure and depth from a few hundred to several thousand meters. In general, shallow reservoirs have greater tendency to fracture, since they have low fracture gradient, ie fractures are formed even with relatively low hydrostatic columns of fluid. These low fracture gradient areas are particularly common in onshore areas, like the Rio Grande do Norte basin. During a well drilling, one of the most favorable phases for the occurrence of fractures is during cementing, since the cement slurry used can have greater densities than the maximum allowed by the rock structure. Furthermore, in areas which are already naturally fractured, the use of regular cement slurries causes fluid loss into the formation, which may give rise to failures cementations and formation damages. Commercially, there are alternatives to the development of lightweight cement slurries, but these fail either because of their enormous cost, or because the cement properties were not good enough for most general applications, being restricted to each transaction for which the cement paste was made, or both reasons. In this work a statistical design was made to determine the influence of three variables, defined as the calcium chloride concentration, vermiculite concentration and nanosilica concentration in the various properties of the cement. The use of vermiculite, a low density ore present in large amounts in northeastern Brazil, as extensor for cementing slurries, enabled the production of stable cements, with high water/cement ratio, excellent rheological properties and low densities, which were set at 12.5 lb / gal, despite the fact that lower densities could be achieved. It is also seen that the calcium chloride is very useful as gelling and thickening agent, and their use in combination with nanosilica has a great effect on gel strength of the cement. Hydrothermal Stability studies showed that the pastes were stable in these conditions, and mechanical resistance tests showed values of the order of up to 10 MPa